Simvastatin-Enriched Macro-Porous Chitosan-Calcium-Aluminate Scaffold for Mineralized Tissue Regeneration - Cassiano,Fernanda Balestrero (2020)
Abstract The present study evaluated the odontogenic potential of human dental pulp cells (HDPCs) exposed to chitosan scaffolds containing calcium aluminate (CHAlCa) associated or not with low doses of simvastatin (SV). Chitosan scaffolds received a suspension of calcium aluminate (AlCa) and were then immersed into solutions containing SV. The following groups were established: chitosan-calcium-aluminate scaffolds (CHAlCa - Control), chitosan calcium-aluminate with 0.5 µM SV (CHAlCa-SV0.5), and chitosan calcium-aluminate with 1.0 µM SV (CHAlCa-SV1.0). The morphology and composition of the scaffolds were evaluated by SEM and EDS, respectively. After 14 days of HDPCs culture on scaffolds, cell viability, adhesion and spread, mineralized matrix deposition as well as gene expression of odontogenic markers were assessed. Calcium aluminate particles were incorporated into the chitosan matrix, which exhibited regular pores homogeneously distributed throughout its structure. The selected SV dosages were biocompatible with HDPCs. Chitosan-calcium-aluminate scaffolds with 1 µM SV induced the odontoblastic phenotype in the HDPCs, which showed enhanced mineralized matrix deposition and up-regulated ALP, Col1A1, and DMP-1 expression. Therefore, one can conclude that the incorporation of calcium aluminate and simvastatin in chitosan scaffolds had a synergistic effect on HDPCs, favoring odontogenic cell differentiation and mineralized matrix deposition.